Neuroprotective effect of angiotensin II type 2 receptor stimulation in vincristine-induced mechanical allodynia - Bessaguet, Flavien; Danigo, Aurore; Bouchenaki, Hichem; Duchesne, Mathilde; Magy, Laurent; Richard, Laurence; Sturtz, Franck; Desmoulière, Alexis; Demiot, Claire (Pain (Amsterdam), 2018)
Peripheral neuropathy is the major dose-limiting side effect of many currently used chemotherapies, such as vincristine (VCR). We recently demonstrated that candesartan, an angiotensin II type 1 receptor antagonist, was neuroprotective against resiniferatoxin-induced sensory neuropathy, and that this effect is mediated by stimulation of the angiotensin II type 2 receptor (AT2R). Thus, we evaluated the effect of preventive treatment with candesartan and a specific AT2R agonist, C21, on a mouse model of VCR-induced neuropathy. Vincristine was administered daily for 7 days to male Swiss mice. Treatment with candesartan and C21 was started on day 1, before VCR treatment, and continued until day 7. We evaluated the development of VCR-induced neuropathy and the effect of treatment by functional tests, immunohistochemical analyses of intraepidermal nerve fibers and dorsal root ganglia neurons, and ultrastructural analysis of the sciatic nerve. Mice treated with VCR showed high mechanical allodynia but no modifications of motor performance or mechanical/thermal nociception. Treatment with candesartan and C21 completely restored normal tactile sensitivity of VCR-treated mice. Both drugs prevented VCR-induced nonpeptidergic intraepidermal nerve fiber loss. Only C21 displayed neuroprotective effects against VCR-induced loss and enlargement of myelinated nerve fibers in the sciatic nerve. Our finding that candesartan and C21 are protective against VCR-induced neuropathic pain through AT2R stimulation favors evaluation of its therapeutic potential in patients receiving chemotherapy.